Efetividade de intervenções na redução do tempo de tela em adolescentes: revisão sistemática - Mendonça, Rafaela Gois de (2021)
Introduction: The rapid technological development, the easy access to electronic devices and their widespread presence in our lives have generated a growing concern regarding the psychological impact caused by the time of exposure to the screen, especially in children and adolescents. Considering the current Pandemic, this time may be even longer. Excessive access to these devices, along with sedentary behavior are associated with harms in physical and mental health. In this context, considering the relationship between the time of exposure to the screen and its consequences on the individual's physical and mental health as an important problem, studying the possible interventions for the prevention and reduction of the time of constant use as well as its effectiveness is extremely important. Objective: To develop a systematic review study in order to assess the effectiveness of interventions in reducing screen time in adolescents. Method: This is a systematic review carried out according to the guidelines of the Preferred Reporting Items for Systematic Reviews and Meta- Analyzes (PRISMA). The PICOS strategy was used to establish the search. The keywords used were: screen time, television, computer, video games, smartphone, adolescents. The databases used were: Cumulative Index to Nursing and Allied Health (CINAHL), U. S. National Library of Medicine (PubMed), PsycINFO (American Psychological Association - APA) and Cochrane Controlled Trials Register. The Boolean operators “AND” and “OR” were used with the keywords to guide the search in the databases. The selection of articles took place in two phases by two researchers, independently and in pairs. The risk of bias was assessed by Cochrane guidelines in Review Manager version 5.5. Results: The initial search resulted in 5,931 articles, after reading titles and abstracts 10 were considered eligible and 4 met the eligibility criteria for inclusion and analysis. The following interventions were used to reduce screen time: dance activity, meditation, physical activity and classroom-level interventions. With regard to the types of screens, the following were addressed in the studies: television, video games, computer and cell phone. Interventions involving physical activity proved to be more effective, however, meditation showed more beneficial effects on secondary outcomes such as decreased smartphone addiction and stress levels, in addition to improving self-control and coping strategies for stress. Conclusion: The interventions used in the studies were partially effective since, after the intervention period, the adolescents showed an increased exposure time, moreover, the fact that this time is self-reported makes it a major limitation of the studies. New randomized clinical trials are needed to assess the effectiveness of interventions aimed at reducing screen time in adolescents, but above all to establish a measurement method with less bias and to follow up so that we can reevaluate the intervention's effectiveness time.